The Role of Sleep Disturbances in Depression and Anxiety: A Literature Review - Aleksandra Kowalczyk (Journal of Education, Health and Sport, 2025)
Background. Sleep disturbances are among the most frequent comorbid symptoms of mood and anxiety disorders. Contemporary evidence indicates they are robust predictors and likely contributory factors in the onset, maintenance, and relapse of these conditions.